Analisis Fenomena Stigma Asal Universitas dalam Proses Rekrutmen Kerja Pada Fresh Graduate - Agnes Suwiko; Siti Nur Fadila; Azra Nur Fahresya; Rafika Meilia Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Discrimination based on university origin remains a phenomenon that influences the recruitmen process in Indonesia. Graduates from non-top-tier higher education institutions often face negative stigma, which limits their job opportunities despite possessing adequate competencies. This research aims to analyze the phenomenon of university origin stigma in the job recruitment process and identify the underlying factors. This study employs a qualitative approach using a literature review method, examining various secondary sources such as scientific journals, labor regulations, and relevant national news. The analysis is conducted to understand the patterns, causes, and impacts of institutional discrimination practices in workforce recruitment. The research findings indicate that university origin stigma is formed through social constructions influenced by the culture of educational hierarchy, perceptions of institutional reputation, and cognitive biases in the selection process by recruiters. This stigma implies inequalities in job access for graduates of non-top-tier higher education institutions and reinforces barriers to social mobility. This research contributes to enriching the study of discrimination in the labor market and emphasizes the importance of reforming the recruitment system to be more objective and competency-based, in order to create a fairer and more inclusive labor ecosystem.